PENERAPAN MODEL FIVES UNTUK MENINGKATKAN KEMAMPUAN LITERASI PESERTA DIDIK PADA MATA PELAJARAN BAHASA INDONESIA KELAS 4 DI SDN KEDUNG BADAK 2 - Melly Safnuryati; Sukmanasa, Elly; Nurul Dhiani, Annisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The FIVES model is one of the learning models related to reading, writing, speaking, listening and viewing. This model also deals with how to manage a reading text that can be used as a guide to make it more meaningful so that it clarifies writing activities clearly. This is closely related to the literacy skills of students who are still relatively low. The pretest results of literacy skills of grade IV students at SDN Kedung Badak 2 showed a low average score. This study aims to determine the improvement of students' literacy skills in learning reading comprehension through the use of the FIVES Model. This research uses PTK where the results of this study show that using this model can improve students' literacy skills.